Acute polyradiculoneuropathy following honey bee sting - Poddar, Karan (Medknow Publications & Media Pvt Ltd, 2012)
Neurological complications following honey bee sting are rare. We report a case of a 3-year-old girl who developed acute polyradiculoneuropathy following honey bee sting, which was diagnosed by nerve conduction studies.